2021
DOI: 10.1111/nyas.14614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating different strategies for poor ovarian response management: a retrospective cohort study and literature review

Abstract: This retrospective study compares four different strategies for managing poor ovarian response (POR), namely, conventional stimulation (300 IUs) IVF-fresh embryo transfer (CONVF), mild stimulation (150 IUs) IVF-fresh embryo transfer (MILDF), mild stimulation embryo banking (MILDB), and embryo banking in natural cycles (NATB). In total, 796 POR patients were considered eligible. Statistical analysis revealed a shorter duration of stimulation and a lower required amount of gonadotropins in MILDF compared with CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It has been proposed that gonadotropins support only the population of follicles that respond to stimulation and do not regenerate follicles in patients with POR. Therefore, the Gn starting dose is not a signi cant factor in determining live birth rates [15][16][17][18][19][20]. A systematic review identi ed no evidence of differences in pregnancy outcomes between low-dose Gn or Gn combined oral agents and high-dose Gn in ovarian stimulation protocols for patients with low ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that gonadotropins support only the population of follicles that respond to stimulation and do not regenerate follicles in patients with POR. Therefore, the Gn starting dose is not a signi cant factor in determining live birth rates [15][16][17][18][19][20]. A systematic review identi ed no evidence of differences in pregnancy outcomes between low-dose Gn or Gn combined oral agents and high-dose Gn in ovarian stimulation protocols for patients with low ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Poor ovarian response (POR) is defined as the collection of three or fewer oocytes in two prior ovarian stimulation cycles, or collection of three or fewer oocytes in a single stimulation cycle from a woman who is over 40 years of age, or collection of three or fewer oocytes in a single stimulation cycle and an abnormal ovarian reserve test (ORT: antral follicle count less than five to seven follicles or anti-mullerian hormone (< 0.5-1.1 ng/mL), or presence of an abnormal ORT in a woman over 40 years of age [1,2] . Patients identified as "poor responders" are an increasing population representing 10 to 24% of women involved in assisted reproductive technology (ART) [3] .…”
Section: Introductionmentioning
confidence: 99%
“…This diverse signaling fund was untapped for IVF until Pantos et al [6] reported the first PRP success in a human fertility context. Since there are several ways to process and administer PRP [7][8][9] it is not surprising that diverse responses have accompanied its use in reproductive practice. However, much can be learned from allied clinical and laboratory experience where PLT handling has been better standardized.…”
Section: Introductionmentioning
confidence: 99%